2009
DOI: 10.1093/pcp/pcp057
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive and High-Throughput Analysis of Plant Hormones Using MS-Probe Modification and Liquid Chromatography–Tandem Mass Spectrometry: An Application for Hormone Profiling in Oryza sativa

Abstract: We have developed a highly sensitive and high-throughput method for the simultaneous analysis of 43 molecular species of cytokinins, auxins, ABA and gibberellins. This method consists of an automatic liquid handling system for solid phase extraction and ultra-performance liquid chromatography (UPLC) coupled with a tandem quadrupole mass spectrometer (qMS/MS) equipped with an electrospray interface (ESI; UPLC-ESI-qMS/MS). In order to improve the detection limit of negatively charged compounds, such as gibberell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
369
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 429 publications
(381 citation statements)
references
References 51 publications
8
369
1
3
Order By: Relevance
“…Extraction and determination of GA of S. moellendorffii microsporangia and young stems were performed using a liquid chromatography-tandem mass chromatography system (AQUITY UPLC System/Quattro Premier XE, Waters) as described 41 . Data were processed by MassLynx software with QuanLynx (version 4.0, Waters).…”
Section: Methodsmentioning
confidence: 99%
“…Extraction and determination of GA of S. moellendorffii microsporangia and young stems were performed using a liquid chromatography-tandem mass chromatography system (AQUITY UPLC System/Quattro Premier XE, Waters) as described 41 . Data were processed by MassLynx software with QuanLynx (version 4.0, Waters).…”
Section: Methodsmentioning
confidence: 99%
“…Extraction and determination of ABA were performed as described previously (Kojima et al, 2009). ABA was measured by ultra-performance liquid chromatography coupled with a tandem quadrupole mass spectrometer equipped with an electrospray interface (Aquity UPLCTM System/Quattro Premier XE; Waters) with an ODS column (Aquity UPLC BEH C 18 [1.7 mm, 2.1 3 100 mm]; Waters).…”
Section: Quantitative Analysis Of Abamentioning
confidence: 99%
“…pollen, and the endogenous GA levels were quantified with ultra-performance liquid chromatography (UPLC)-tandem mass spectrometry (Kojima et al, 2009). The results indicated that the dominant bioactive GAs in pollen were GA 4 and GA 7 and that the levels significantly increased during pollen maturation under normal conditions (Fig.…”
Section: Lt Reduces the Endogenous Levels Of Bioactive Gas In Developmentioning
confidence: 99%
“…GAs were extracted from 100 mg of cv Sasanishiki anthers dissected at meiotic, uninucleate, binucleate, and trinucleate pollen stages with or without LT treatment, and their identities were determined using UPLC-tandem mass spectrometry (AQUITY UPLC System/XEVO-TQS; Waters) with an octadecylsilyl column (AQUITY UPLC BEH C18, 1.7 mm, 2.1 3 100 mm; Waters) as described previously (Kojima et al, 2009). Each series of experiments was performed in biological triplicate.…”
Section: Quantification Of Gasmentioning
confidence: 99%